La invención como forma del pensamiento: entrevista a B. Ruby Rich - Smiraglia, Romina; Acosta, Fermín; Invernizzi, Agostina; Martinelli, Lucas (Imagofagia, 2021)
Entrevista a B. Ruby Rich. Abstract: Interview to B. Ruby Rich.